Genetic Analysis of Candida albicans Filamentation by the Iron Chelator BPS Reveals a Role for a Conserved Kinase—WD40 Protein Pair - Mariel Pinsky; Daniel Kornitzer (Journal of Fungi, 2024)
Candida albicans is a major human pathogenic fungus that is distinguished by its capability to switch from a yeast to a hyphal morphology under different conditions. Here, we analyze the cellular effects of high concentrations of the iron chelator bathophenanthroline disulfonate (BPS). BPS inhibits cellular growth by withholding iron, but when iron chelation is overcome by the addition of hemoglobin as an iron source, the cells resume growth as hyphae. The BPS hyphal induction pathway was characterized by identifying the hyphal-specific transcription factors that it requires and by a forward genetic screen for mutants that fail to form hyphae in BPS using a transposon library generated in a haploid strain. Among the mutants identified are the DYRK1-like kinase Yak1 and Orf19.384, a homolog of the DYRK1-associated protein WDR68/DCAF7. Orf19.384 nuclear localization depends on Yak1, similar to their mammalian counterparts. We identified the hyphal suppressor transcription factor Sfl1 as a candidate target of Yak1-Orf19.384 and show that Sfl1 modification is similarly affected in the yak1 and orf19.384 mutant strains. These results suggest that DYRK1/Yak1 and WDR68/Orf19.384 represent a conserved protein pair that regulates cell differentiation from fungi to animals.